Phosphorus–nitrogen compounds. Part 58. Syntheses, structural characterizations and biological activities of 4-fluorobenzyl-spiro(N/O)cyclotriphosphazene derivatives. Issue 1 (2nd January 2023) - Binici, Arzu; Elmas, Gamze; Okumuş, Aytuğ; Erden Tayhan, Seçil; Hökelek, Tuncer; Şeker, Büşra Nur; Açık, Leyla; Kılıç, Zeynel
Abstract: The starting compound, tetrachloro-4-fluorobenzyl-spiro(N/O)cyclotriphosphazene (2 ), was synthesized from the substitution reaction of hexachlorocyclotriphosphazatriene (N3 P3 Cl6 ; trimer; HCCP ) with sodium 3-(4-fluorobenzylamino)-1-propanoxide (1 ). Reactions of spiro (2 ) with excess 1-(2-aminoethyl)-piperidine, 4-(2-aminoethyl)-morpholine, 1-(2-hydroxyethyl)piperidine and 4-(2-aminoethyl)morpholine yielded the fully substituted cyclotriphosphazene derivatives (2a–2d ), respectively. Elemental analysis, mass spectrometry (ESI-MS), FTIR, 1 H-, 13 C- and 31 P-NMR data confirmed the structure of the new cyclotriphosphazenes (2a–2d ); and the crystal structure of 2 was also identified by X-ray crystallography. The quantum mechanical DFT calculations of 2 were performed to estimate the geometry optimization, total energy, orientation of frontier molecular orbitals (HOMOs and LUMOs), and chemical parameters. In addition, antibacterial and antifungal activities of the fully substituted 4-fluorobenzyl-spiro(N/O)cyclotriphosphazenes (2a–2d ) were investigated against G(+) and G(−) bacteria and fungi. Using agarose gel electrophoresis, the DNA cleavage activities of these phosphazenes on double-stranded plasmid DNA were evaluated. To evaluate the abilities of compounds 2a–2d to inhibit cell proliferation in different concentrations, the antiproliferative and antimigrative activities against prostate adenocarcinoma (PC3), breast cancer (MCF7) and colon cancer (HT29) cell lines were studied in vitro ; and the compound 2c was determined to be the most efficient against the three cancer cells. Communicated by Ramaswamy H. Sarma Graphical Abstract: UF0001